Analisis Penggunaan Bahasa dalam Artikel Promosi Wisata Pulau Bedil di Media Daring Banyuwangi - Zahra Al Muhdlar, Hanina; Weni Febriyanti; Novi Afriliya; Mohamad Afrizal (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to analyze the language strategies used in promotional articles about Bedil Island tourism published in local Banyuwangi online media and how the language forms the representation of the image of the tourist destination. Bedil Island is one of the new tourist destinations that is developing and starting to be known to the wider community, especially through online media coverage. Through a qualitative approach with a literature study method, this study examines two promotional articles about Bedil Island tourism published by different local sites. The results of the analysis show that the language strategies used include the use of metaphors, local origin narratives, strong visual descriptions, and the insertion of quantitative data to build the credibility of the information. Phrases such as “Banyuwangi's Raja Ampat” and “hidden natural lagoon” play an important role in building the reader's imagination of the beauty and exclusivity of Bedil Island. The representation of the image of Bedil Island is also formed through a combination of emotional, ecological, and rational aspects presented in the text. This study shows that the language in promotional articles is not neutral, but is used strategically to shape the perception and image of the destination in the minds of the audience. Therefore, understanding the use of language in tourism promotion is important, especially in the context of sustainable local tourism development.